Salivary gland of Toxorhynchites splendens Wiedemann (Diptera: Culicidae): Ultrastructural morphology and electrophoretic protein profiles - Jariyapan N. (2014)
The salivary glands of male and female Toxorhynchites splendens have the same morphology, and they are paired organs lying on either side of the esophagus. Each gland is composed of two identical tubular lobes, joined together at the end of the proximal region. In the gland, a salivary duct extends through the length of each lobe. The general cellular architecture of the salivary gland of this mosquito is unique. No secretory cavity was found in any cell, and the salivary materials are secreted from long microvilli and collect in a periductal space surrounding the duct. In addition, a number of mitochondria, rough endoplasmic reticulum, and a very large nucleus were observed, suggesting a high energy requirement for producing the salivary proteins involved in sugar feeding. The size of the gland is ≈50 μm in diameter and 1.5 mm in length. These dimensions correlate with high protein content of these salivary glands (2.88 ± 0.14 μg/gland pair). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis revealed that the electrophoretic protein profiles of the male and female salivary glands were identical. No dominant major proteins were found. Compared with Aedes and Anopheles mosquitoes, the protein profile of T. splendens was similar to that observed in the males of these other species but different to that shown by the females, thus making T. splendens an excellent organism for studying the biochemistry of sugar feeding in mosquitoes.